Estabilidad productiva de variedades de raigrás anual - Mendez, Daniel Gustavo; Frigerio, Karina Laura; Ruiz, Maria De Los Angeles; Fontana, Laura María Celia; Iacopini, Maria Lorena; Carassai, Ainalén Ligia; Barbera, Pablo; Re, Alejo Esteban; Otondo, Jose; Cicchino, Mariano Andres; Bailleres, Matias Andres; Andersen, Martin; et al. (Asociación Argentina de Producción Animal (AAPA), 2025)
Publicado en: Revista de Producción Animal, v. 45, suplemento 1 : 191 (2025)